Using Decision Tree Technique to Predict the Financial Collapse of Iraqi Private Banks: An Applied Study - Karrar Kareem Jawad; Enaam Kareem Jawad; Hakeem Hammood Flayyih (Technium EconomiA, 2024)
Predicting the Financial Collapse (FC) using modern technologies and scientific methods for Iraqi private banks is considered an early warning to detect their failure in the future. Therefore, these proposals, represented by scientific methods and modern technologies, are submitted to the specialized bodies represented by (the Central Bank of Iraq) in order to present them to the banks in the research sample to raise their capacity through the use of modern technologies and in order to adopt them as a scientific basis for predicting the FC. The following will be followed: Evaluating the performance of banks and classifying them based on the Camels standard (CS) and predicting the FC based on modern technologies (by relying on the decision tree algorithm). The research relied on the deductive approach to complete the theoretical aspect and the applied (experimental) approach to complete the practical aspect. The researcher also processed and prepared the data and then evaluated the performance of banks and classified them based on the CS equations consisting of five indicators and on the averages of these results as inputs for prediction using DT. Different computer programs were also adopted, as the Excel program was used to unload the data, the (SPSS) program to apply the equations, and the (Matlab) program to predict modern technologies. The most prominent conclusions reached by the research are as follows: Modern technologies represented by decision trees are characterized by providing more accurate information